Pengaruh Kesadaran Wajib Pajak, Pengetahuan Pajak, Sanksi Pajak Dan Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kota Medan - Yois Nelsari Malau; Theresia Lumban Gaol; Ehtri Novelia Giawa; Chesya Juwita (Ekonomis: Journal of Economics and Business, 2021)
Tax is one of the payments to the State which is paid by a person or entity. Therefore, consistency with paying taxes is very important to build state revenue. This test aims to determine the effect of taxpayer awareness, knowledge of taxes, tax sanctions and tax services on taxpayer compliance with motorized vehicles in the city of Medan. The population that we use for this study are taxpayers who are registered with the Samsat of Medan City. The sample in this study was 100 respondents with an examination strategy using the accidental sampling method. The information used in this study is important information from the appropriate survey results and interviews with interviews. The test strategy uses Validity and Reliability testing, Classical Assumption Test and Hypothesis Determination Coefficient. The results of this investigation trace that taxpayer awareness factors, tax knowledge, tax sanctions and tax service services have an influence on compliance with motorized vehicle registration in the city of Medan. The results of this examination, it is natural that the Medan City Samsat office can further develop its performance so that it can improve the consistency of citizens to pay their taxes.